2016
DOI: 10.4187/respcare.05002
|View full text |Cite
|
Sign up to set email alerts
|

Veteran Preferences Regarding Wireless Management of Positive Airway Pressure for Obstructive Sleep Apnea at a Tertiary Health-Care System

Abstract: PAP data download preferences were mixed among new veteran users. Veterans placed a high value on the potentially competing concerns of convenience and information privacy. Veterans preferring modem factored convenience as important in their decision making, independent of privacy concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…7,44,76 For those patients who are doing well with their positive airway pressure therapy (or other treatments), a simple tele-health visit or Internet-based communication could suffice, leaving more time for patients with more complex problems to be evaluated in an office setting. 158 Also, self-monitoring of blood pressure and weight is gaining interest. Mendelson and colleagues 159 showed the feasibility of patient entry of blood pressure, CPAP use, sleepiness and quality of life data for clinician review, and McManus and colleagues 160 reported that patient self-monitoring of blood pressure, with or without telemonitoring, decreased blood pressure values after 1 year.…”
Section: Management Outside the Officementioning
confidence: 99%
“…7,44,76 For those patients who are doing well with their positive airway pressure therapy (or other treatments), a simple tele-health visit or Internet-based communication could suffice, leaving more time for patients with more complex problems to be evaluated in an office setting. 158 Also, self-monitoring of blood pressure and weight is gaining interest. Mendelson and colleagues 159 showed the feasibility of patient entry of blood pressure, CPAP use, sleepiness and quality of life data for clinician review, and McManus and colleagues 160 reported that patient self-monitoring of blood pressure, with or without telemonitoring, decreased blood pressure values after 1 year.…”
Section: Management Outside the Officementioning
confidence: 99%